Economic Consequences of Political Persecution - Radim Bohacek; Michal Myck (Institute of Labor Economics (IZA), 2017)
We analyze the effects of persecution and labor market discrimination during the communist regime in the former Czechoslovakia using a representative life history sample from the Survey of Health, Ageing and Retirement in Europe. We find strong effects of persecution and dispossession on subsequent earnings, with most severe implications of job loss due to persecution on earnings in subsequent jobs and on career degradation. Accumulated long-term effects in the form of initial retirement pensions paid during the communist regime are even greater. These pension penalties disappear by 2006 largely as a result of compensation schemes implemented by democratic governments after 1989. We use unique administrative data on political rehabilitation and prosecution to instrument for the endogenous variables. Finally, we survey transitional justice theory and document reparations programs in other countries.
Keywords: N34; J70; J31; C21; 330; life histories; wage differentials; persecution; labor discrimination; economic history; treatment effect models